2020
DOI: 10.1111/febs.15443
|View full text |Cite
|
Sign up to set email alerts
|

Novel FMRP interaction networks linked to cellular stress

Abstract: Silencing of the fragile X mental retardation 1 (FMR1) gene and consequently lack of synthesis of FMR protein (FMRP) are associated with fragile X syndrome, which is one of the most prevalent inherited intellectual disabilities, with additional roles in increased viral infection, liver disease, and reduced cancer risk. FMRP plays critical roles in chromatin dynamics, RNA binding, mRNA transport, and mRNA translation. However, the underlying molecular mechanisms, including the (sub)cellular FMRP protein network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 181 publications
(252 reference statements)
0
36
0
Order By: Relevance
“…Barceló et al [34] reported that HNRNPA2B1 acts as a regulator of KRAS-dependent tumorigenesis through the critical pancreatic ductal adenocarcinoma cells signaling pathway PI3K/AKT. FMR1 gene and consequently lack of synthesis of FMR protein (FMRP) is associated with fragile X syndrome, and FMRP plays a critical role in chromatin dynamics, RNA binding, mRNA transport, and mRNA translation [35,36]. Jianhao Li et al [37] indicated that high expression of KIAA1429 and HNRNPA2B1 were signi cantly associated with poor prognosis in osteosarcoma, and m 6 A regulators might be involved in osteosarcoma progression through humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Barceló et al [34] reported that HNRNPA2B1 acts as a regulator of KRAS-dependent tumorigenesis through the critical pancreatic ductal adenocarcinoma cells signaling pathway PI3K/AKT. FMR1 gene and consequently lack of synthesis of FMR protein (FMRP) is associated with fragile X syndrome, and FMRP plays a critical role in chromatin dynamics, RNA binding, mRNA transport, and mRNA translation [35,36]. Jianhao Li et al [37] indicated that high expression of KIAA1429 and HNRNPA2B1 were signi cantly associated with poor prognosis in osteosarcoma, and m 6 A regulators might be involved in osteosarcoma progression through humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of FMRP-binding proteins in neuronal and other tissues has identified numerous interacting partners. Interestingly, among these interacting partners are the proteins Caprin1 and G3BP that have independently been implicated in the induction of the ISR pathway in response to stress (Taha MS et al, 2020; Wu Y et al, 2016). Pertinently, both Caprin1 and G3BP1 have been shown to be important for eIF2α phosphorylation (Reineke LC et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The R138Q mutation resides within the extreme C-terminus of this domain and this mutant does not support FMRP-dependent roles in the DNA damage response of cells. Furthermore, the FMRP N-terminus interacts with at least 76 different proteins (46), including CYFIP1/2 and NUFIP1/2 (47)(48)(49). While the cellular role of most of these proteins are still unclear, CYFIP1/2 are key components of the Wave Regulatory Complex required for actin remodelling (50,51).…”
Section: Discussionmentioning
confidence: 99%